Principles of comparative religious education in the Qur’an - Hashi, Abdurezak Abdulahi (2009)
The Qur’an, which is the founding Scripture of Islam, acknowledges the existence of various religious scriptures and holy texts (Îuhuf and kutub), faiths and beliefs (iman and aqa’id), rituals and social laws (ibadat and shara’i), way of life and cults (mansakan wa manhajan) and historical events and narratives (al-anba’ wa al-qasas). European Orientalists like Weitbrecht Stanton commented on the Qur’anic explanation of religious faiths and religious communities and concluded that: “No Scripture in the world teaches such a ‘comparative religion as the Qur’Én.”. Furthermore, not only the Qur’Én acknowledges such faiths and holy scriptures, it also provides the elementary perceptions about the earliest doctrinal creeds, rites and rituals of man, and presents a number of religious terms such as millah, dÊn and ummah, which more or less contain the meanings of “religion” and religious “communities”. Likewise, the Qur’an offers some fundamental principles of how to deal with other religions and other religious communities, in terms of understanding and studying their belief systems, and in terms of having social and intercultural relations with them. Among such principles are intellectual honesty, continues religious dialogue, objective and accommodative behaviour, and finally, the need for accuracy and evidence based judgment about other faiths. Through analytical and textual methods, this paper aims to expose the Qur’anic foundations and principles of comparative religious education (ilm darasat al-adyan).